COMPARATIVE CHARACTERISTICS OF THE MEANS PREVENTING THE APPEARANCE OF THE INHIBITED LAYER ON THE SURFACE OF THE COMPOSITE - V. V. Tairov; A. A. Arutunova; K. K. Egunyan; I. O. Kamyshnikova; V. A. Ivashchenko; S. I. Risovannyj (Кубанский научный медицинский вестник, 2018)
Aim. This study was designed to evaluate the effectiveness of preventing the formation of a layer inhibited by oxygen or reducing its amount using various means.Materials and methods. The study was performed at the Department of Therapeutic Dentistry of the FSBEI HE KubSMU of the Ministry of Health care of Russia and the laboratory instrument factory "Cascade", Krasnodar. The composite Filtek Ultimate (3M ESPE, USA) was used for the production of model samples by placing the composite material in clean plastic molds with a diameter of 13.5 mm, thickness of 4 mm and polymerization, the following materials were selected to prevent contact of oxygen with the surface of the composite: glycerin solution, lavsan plate, Teflon tape. For the comparison with the standard method of elimination of the layer inhibited by oxygen we used the finishing of the surface of the composite. The surface hardness of the samples of each group and subgroup was measured using the apparatus-hardness tester PMT-3 by the Vickers method. The multivariate analysis of variance (ANOVA) was conducted in Statistica software 13. The samples were stained separately with a solution of "Lipton" tea from 2015 for 3 years. The degree of pigment deposition was evaluated.Results. The determining factor in the long-term functioning of the composite restoration is the stability of the surface layer. The results of the study showed the lowest microhardness of the samples from the group without any blockers of oxygen penetration without finishing (56HV), the highest microhardness was in samples from the group covered with Teflon tape with finishing (107HV). The probability value p<0.05 was obtained for all study groups. The results of the color change of the restoration were evaluated in the coloring medium. The assessment of changes in the coloring was carried out for 3 years. The results of staining allowed to confirm the obtained data of the study: 1) the intensity of staining of all samples increases over time, 2) the samples from the groups without glycerin coating were stained to a greater extent before the polymerization, without finishing in comparison with the samples from the groups without glycerin but with finishing, 3) the sample with glycerin coating and finishing was stained the least.Conclusion. Thus, the results of the study allow us to recommend using the means preventing the formation of the oxygeninhibited later to improve the efficiency of the restoration of the composite and increase the duration of its functioning. Depending on the clinical situation, glycerin, lavsan plate or Teflon tape can be used as oxygen blockers.